Analysis of Phonetics Error in learning Arabic second Langue And proposed solutions: Case of Zarma-Songhay Students (Contrastive Analysis Study) - Nouroudine Abdoulaye Mamoudou (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2021)
This study aims to analysis the Phonetics errors of the Zarma-Songhai students during their studies of Arabic as a second language, after observing many problems that these students face during the pronunciation of some Arabic sounds such as Ø§Ù„Ø®Ø§Ø¡ /Ø®/ ÙˆØ§Ù„Ø¶Ø§Ø¯ /Ø¶/ ÙˆØ§Ù„ØµØ§Ø¯ /Øµ/...ØŒ. The study was limited to analyzing the vowels and consonants sounds without bend to other phonological or linguistical errors, and we adopted a contrastive analysis approach to compare the sounds between Arabic and Zarma-Songhai, to find out the common, similar or different sounds between the two languages, and we have reached (16) common sounds, and (12) missing Arabic sounds in the Songhai language. It is where the students faces difficulty in acquiring this sounds, and the most difficult among them are the sounds of the â€œtip of the tongue and above the foldsâ€ sounds witch are : / Øµ /, / Ø¶ /, / Ø·/ and the sounds of the â€œtip of the tongue and the edges of the soundsâ€ like/ Ø¸ /, / Ø« /, / Ø° /. Then we monitored the students' mistakes according to the error analysis approach (identifying, explaining, and correcting the error). Finally, we presented many ways to solve sound problems of phonetics errors and some vocal training models such as Minimal-PairsÂ ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ ØªØÙ„ÙŠÙ„ Ø£Ø®Ø·Ø§Ø¡ Ø·Ù„Ø§Ø¨ Ø§Ù„Ø²Ø±Ù…Ø§-Ø§Ù„Ø³Ù†ØºØ§ÙŠ Ø¹Ù†Ø¯ ØªØ¹Ù„Ù…Ù‡Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØºØ© Ø«Ø§Ù†ÙŠØ©ØŒ ÙˆØ°Ù„Ùƒ Ø¨Ø¹Ø¯ Ù…Ù„Ø§ØØ¸Ø© Ø§Ù„Ø¹Ø¯ÙŠØ¯ Ù…Ù† Ø§Ù„Ù…Ø´Ø§ÙƒÙ„ Ø§Ù„ØªÙŠ ÙŠÙˆØ§Ø¬Ù‡Ù‡Ø§ Ù‡Ø¤Ù„Ø§Ø¡ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø²Ø±Ù…Ø§- Ø³Ù†ØºØ§ÙŠ Ø¹Ù†Ø¯ Ù†Ø·Ù‚ Ø¨Ø¹Ø¶ Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ø«Ù„: Ø§Ù„Ø®Ø§Ø¡ /Ø®/ ÙˆØ§Ù„Ø¶Ø§Ø¯ /Ø¶/ ÙˆØ§Ù„ØµØ§Ø¯ /Øµ/...ØŒ ÙˆØ§Ù‚ØªØµØ±Øª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¹Ù„Ù‰ ØªØÙ„ÙŠÙ„ Ø£ØµÙˆØ§Øª Ø§Ù„Ø¸ÙˆØ§Ù‡Ø± Ø§Ù„Ù‚Ø·Ø¹ÙŠØ© Ø¯ÙˆÙ† ØºÙŠØ±Ù‡Ø§ Ù…Ù† Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„ØµÙˆØªÙŠØ© Ø£Ùˆ Ø§Ù„Ù„ØºÙˆÙŠØ©ØŒ ÙˆÙ‚Ø¯ Ø§Ù†ØªÙ‡Ø¬Ù†Ø§ Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„ØªÙ‚Ø§Ø¨Ù„ÙŠ Ù„Ù„Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨ÙŠÙ† Ø§Ù„Ø£ØµÙˆØ§Øª ÙÙŠ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„Ø²Ø±Ù…Ø§-Ø³Ù†ØºØ§ÙŠ Ù„Ù…Ø¹Ø±ÙØ© Ø§Ù„Ø£ØµÙˆØ§Øª Ù…Ø´ØªØ±ÙƒØ© ÙˆÙ…ØªØ´Ø§Ø¨Ù‡Ø© Ø£Ùˆ Ù…Ø®ØªÙ„ÙØ© Ø¨ÙŠÙ†Ù…Ù‡Ø§ØŒ ÙˆÙ‚Ø¯ ØªÙˆØµÙ„Ù†Ø§ Ø¥Ù„Ù‰ ÙˆØ¬ÙˆØ¯ (16) ØµÙˆØªØ§ Ù…Ø´ØªØ±ÙƒØ©ØŒ Ùˆ (12) ØµÙˆØªØ§ Ø¹Ø±Ø¨ÙŠØ© Ù…ÙÙ‚ÙˆØ¯Ø© ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø³Ù†ØºØ§ÙŠ. ÙˆÙ‡ÙŠ Ø§Ù„ØªÙŠ ÙŠÙˆØ§Ø¬Ù‡ ÙÙŠÙ‡Ø§ Ø§Ù„Ø¯Ø±Ø§Ø³ ØµØ¹ÙˆØ¨Ø© ÙÙŠ Ø§ÙƒØªØ³Ø§Ø¨Ù‡Ø§ØŒ ÙˆØ£Ù† Ø£ØµØ¹Ø¨Ù‡Ø§ Ø¹Ù„ÙŠÙ‡Ù… Ù‡ÙŠ Ø£ØµÙˆØ§Øª Ù…Ø®Ø§Ø±Ø¬